PENGARUH LITERASI KEUANGAN, MOTIVASI INVESTASI DAN RETURN INVESTASI TERHADAP MINAT INVESTASI SAHAM PADA GENERASI Z - Herlinda Maya Kumala Sari; Muhammad Shalahudin Hidayat; Detak Prapanca (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to identify and analyze the influence of financial literacy, investment motivation, and investment returns on stock investment interest among Generation Z in Mojokerto City. This study uses a quantitative method by distributing questionnaires to the residents of Mojokerto City. The population in this study consists of residents in Mojokerto City, with the sample taken being residents who have an interest in conducting stock investment activities and those who have already engaged in stock investment activities. The sampling technique used is non-probability sampling with purposive sampling, involving 127 respondents. The sampling criteria in this study are Generation Z residents, both male and female, who have shown interest in conducting stock investment activities and those who have already engaged in stock investment activities, as well as possessing a SID (Single Investor Identification). The data analysis technique uses Partial Least Square (PLS) with SmartPLS version 3.0 software, and the measurement model is evaluated using Outer Model and Inner Model. The results of this study show that financial literacy does not have a significant effect on stock investment interest in Mojokerto City. Investment motivation does not have a significant effect on stock investment interest in Mojokerto City. Investment returns have a significant effect on stock investment interest in Mojokerto City.